Transmission of Environmental Values in Wawacan Sulanjana for Majalengka Community - Nur Rochmansyah, Bagaskara; Supriyanto, RM. Teguh; Doyin, Mukh (Seloka: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2023)
Majalengka community has been intertwined with environmental issues for many years. It can be observed through oral literature Gaok, specifically in a manuscript entitled Wawacan Sulanjana. The manuscript talks about Nyi Puhaci who reincarnated as various plants, taking care and maintaining the environment. This study proposes to reveal the transmission of environmental value in Wawacan Sulanjana for Majalengka community using Bascoms' theory. This study applied a folklore approach. It used the first reading technique of semiotics (heuristic) to compile the data. Furthermore, the second technique of semiotics (hermeneutic) was utilized to analyze the data. In this study, the data were lines and stanzas from Wawacan Sulanjana manuscript. The results demonstrated that Wawacan Sulanjana contains a function of food security system. The manuscript has a transmission that people must be in hands to reach common good. Moreover, the food security system has to maintains over generations. In this context, upholding religious teachings fundamental to contributing for mutual benefits. This manuscript transmits the urgency of knowledge in farming to preserve food security. The system must be focus too fairly and responsibly.